The Influence of Perception Price, Perception Quality And Product Design On Repurchase Intention With Perception Value As A Mediation Variable (Case Study Of Brand Mulia Ceramic Consumer In Bandung City) - Arizal Muzahiddan; Fansuri Munawar (Dinasti Publisher, 2025)
This research aims to examine the influence of price perception, quality perception and product design on repurchase intention with value perception as a mediating variable. The research method used is quantitative with a descriptive verification approach. Researchers use non-probability sampling techniques, namely sampling techniques that do not provide opportunities or opportunities for each member of the population to be selected as a sample. This study selected a sample of 100 people. The tool used to analyze the data in this research is SmartPLS 4. The research results show that (1) price perception has a positive effect on value perception, (2) perception has no positive effect on value perception, (3) product design has a positive effect on value perception, (4) price perception has a positive effect on repurchase interest, (5) quality perception has no positive effect on repurchase interest (6) product design has no positive effect on repurchase interest (7) value perception has a positive effect on repurchase intention, (8 ) price perception has a positive effect on repurchase interest through perceived value, (9) Quality perception does not have a positive effect on repurchase interest through value perception, (10) Product design has a positive effect on repurchase interest through value perception.